Ulasan Undang-Undang No.17 Tahun 2023 Tentang Kesehatan - Satria Indra Kesuma (Jurnal Nusantara Berbakti, 2024)
This Community Service Program aims to provide information about the legal protection of doctors, and health workers in providing optimal health services. The results of community service outline various factors such as workload, availability of medical facilities and equipment, as well as policies that value work-life balance, into important aspects discussed. In overcoming the challenges of high workloads and maintaining quality of services, it is important for hospitals and relevant stakeholders to create a supportive environment, including providing adequate facilities and implementing policies that take into account doctors' work-life and personal life balance. The benefits of this program provide richer insight into legal protection issues and convenience in practicing medicine in hospitals and their impact on the quality of health services provided by doctors.